Psychological readiness to return to the slopes following serious injury among competitive skiers and snowboarders - Leslie Podlog; Jeffrey G. Caron; Bradley Fawver; John J. Fraser; Quinn Johnsson; Miriam H. Beauchamp; Marie-Lyne Nault (Elsevier, 2023)
Introduction: Despite the traditional focus on assessment of athletes' physical readiness to return to sport, mounting evidence suggests that consideration of psychological readiness is critically important in ensuring that individuals safely and effectively resume competitive activities. Objectives: The primary aims of this article are to: (1) evaluate existing measures assessing psychological readiness; among skiers and snowboarders (the focus of this special issue); (3) discuss biopsychosocial factors that facilitate or undermine psychological readiness; and (4) highlight implications of psychological readiness for return to sport outcomes and articulate future research directions. Methods: A literature search was performed in Scopus, PsycInfo, and PubMed using the keywords "psychological readiness," "ski injuries," "snowboard injuries," "return to sport," and "concussions." Results: Existing measures of psychological readiness are limited by conceptual ambiguities and measurement shortcomings. Limited research with skiers and snowboarders suggests that cognitive, affective, and behavioral elements of psychological readiness outlined in past work is apparent among skiers. Physical (issue healing and body system recovery), psychological (personality, recovery motivation), and social (social support, trust in rehabilitation providers) factors can facilitate or undermine psychological readiness. Psychological readiness predicts salient postinjury outcomes, such as the likelihood of returning to sport, reinjury, as well as the quality of postinjury performance. Conclusions: Future research is needed to further delineate the nature of psychological readiness among skiers and snowboarders. Existing evidence, however, suggests a variety of biopsychosocial factors contribute to athletes' psychological readiness which may be a key predictor of salient postinjury outcomes.